2018
DOI: 10.2478/njmr-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Ageing Body as a Bordering Site: <i>Narrowing definitions of dependency for elderly family reunification in Finland</i>

Abstract: This article explores how the concept of dependency is used when scrutinising residence permit applicants of the elderly who fall into the category of "other family members" for family reunion. Through an analysis of interviews with immigration officers, as well as Finnish and European Union (EU) legal documents, the article shows that contestations of the concept of dependency become part of bordering practices. Bordering thus enters the everyday lives of transnational families with elderly family members in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The initial interest in studying the experiences of older migrants was based on earlier research which on the one hand had indicated the presumed "double-jeopardy" of older migrants as vulnerable both due to their position as migrants as well as their age (King, Lulle, Sampaio, & Vullnetari, 2017;also, Grenier et al, 2017) and on the other hand, the elevated expectations of migrants regarding their performance as selfreliant "good citizens" (Anderson, 2013). Revealing vulnerability may indeed hold a particular stigma for migrants who are expected to demonstrate self-reliance and productivity, or risk being deemed "undeserving" (Pellander, 2018). However, our sample included individuals in relatively advantageous positions.…”
Section: Analysing Written Narrativesmentioning
confidence: 99%
“…The initial interest in studying the experiences of older migrants was based on earlier research which on the one hand had indicated the presumed "double-jeopardy" of older migrants as vulnerable both due to their position as migrants as well as their age (King, Lulle, Sampaio, & Vullnetari, 2017;also, Grenier et al, 2017) and on the other hand, the elevated expectations of migrants regarding their performance as selfreliant "good citizens" (Anderson, 2013). Revealing vulnerability may indeed hold a particular stigma for migrants who are expected to demonstrate self-reliance and productivity, or risk being deemed "undeserving" (Pellander, 2018). However, our sample included individuals in relatively advantageous positions.…”
Section: Analysing Written Narrativesmentioning
confidence: 99%
“…This scholarship has shown that through gendered, racialized, and classed "moral gatekeeping" (Wray 2006), conceptions of "proper" loving, marrying and parenting are mobilized by state actors to define who may be part of the national community and who may not (Author's reference C). Overall, this scholarship on law and politics has zeroed in on state controls of the "legitimacy" and "veracity" of coupledom and -to a lesser extent -motherhood and fatherhood, with very few studies exploring the (non)admission of family members beyond the so-called "nuclear" family (however, on admission of elderly parents see Bonizzoni 2018, 224, 232;Pellander 2018). This contrasts with the sociological and anthropological "transnational families" literature, which "embraces a wide definition of the family including interand intra-generational relationships beyond nuclear families" (Merla, Kilkey, and Baldassar 2020, 397).…”
Section: Conceptualizing Family In Migration Scholarship and Politics...mentioning
confidence: 99%
“…In line with this interpretation of the Strasbourg jurisprudence, the Dutch term used in these guidelines to refer to "mtnet" is not a literal translation, but avoids the "confusing" reference to emotions to center dependency instead. In Dutch, mtnet is referred to as "een meer dan gebruikelijke afhankelijkheidsrelatie" which translates as "a relationship of more than usual dependency" (IND 2022a, 1-2; for an analysis of a very similar use of the concept of "dependency" in the (non-)admission of elderly in Finland, see Pellander 2018).…”
Section: Suffering Relativesmentioning
confidence: 99%
“…While the 'tactics of everyday life' (de Certeau 1984) utilised by women engaged in commercial sex (Diatlova & Näre 2018) differ fundamentally from those of elderly family migrants (Pellander 2018), or -for instance -from those of irregular migrants with health concerns (Bendixsen 2018), in each case, bordering practices produce latent -and often also actual -problems and risks. At the same time, as Sager ( 2018) argues, migrant tactics of coping and resistance can also affect bordering practices, constituting potential 'acts of citizenship' (Isin 2008).…”
Section: Migrants and Gatekeepersmentioning
confidence: 99%
“…Another case of bordering practices affecting citizens is Pellander's (2018) analysis of Finnish policies and practices regarding family reunion for elderly family members living abroad. In order for elderly parents or grandparents to be allowed entry, they must prove total dependency on the family member living in Finland.…”
Section: Contributions To the Special Issuementioning
confidence: 99%